SARS-CoV-2 Molecular Network Structure - Díaz, José (Frontiers in Physiology, 2020)
The knowledge about the molecular basis of SARS-CoV-2 infection is incipient. However, recent experimental results about the virus interactome have shown that this single-positive stranded RNA virus produces a set of about 28 specific proteins grouped in: 16 nonstructural proteins (Nsp1 to Nsp16), four structural proteins (E, M, N, S) and eight accessory proteins (orf 3a, orf6, orf7a, orf7b, orf8, orf9b, orf 9c and orf10). In this brief communication, the network model of the interactome of these viral proteins with the host proteins is analyzed. The statistical analysis of this network shows that it has a modular scale-free topology in which the virus proteins orf 8, M and Nsp7 are the three nodes with more connections (links). This result suggests the possibility that a simultaneous pharmacological attack on these hubs could assure the destruction of the network and elimination of the virus.